2016
DOI: 10.1111/ijfs.13039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and modelling of natural convection and conduction heat exchange: study on food systems with modified starch by means of computational fluid dynamics

Abstract: This study is focused on the effects of starch gelatinisation on heat exchange in food systems containing four modified starch concentrations (0, 2, 6 and 10%). Viscosity profiles of samples were experimentally measured: the effect of gelatinisation was evident, particularly at 6% and 10%, where the viscosity increased from 0.010 to 70 Pa s and to 1507 Pa s, respectively. The heat exchange rate showed a decrease with the increasing of starch concentration, and the effects were observed until 6%. Four Computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Earlier researches conducted on sterilization of solid foods such as canned tuna, purees, thick syrups, and concentrates were assumed to be through conduction heat transfer only, and similar to this study, SHZ was located at the geometric center of the container (Cordioli et al, 2016;Rinaldi et al, 2018;Varma & Kannan, 2006). In studies conducted by Vatankhah et al (2015), Vatankhah et al (2016), they found out that SHZ locations in Haleem and apple puree were packaged in semirigid aluminum containers, remained fixed at the geometric center of the container (Vatankhah et al, 2015(Vatankhah et al, , 2016.…”
Section: Re Sults and Discussionsupporting
confidence: 57%
“…Earlier researches conducted on sterilization of solid foods such as canned tuna, purees, thick syrups, and concentrates were assumed to be through conduction heat transfer only, and similar to this study, SHZ was located at the geometric center of the container (Cordioli et al, 2016;Rinaldi et al, 2018;Varma & Kannan, 2006). In studies conducted by Vatankhah et al (2015), Vatankhah et al (2016), they found out that SHZ locations in Haleem and apple puree were packaged in semirigid aluminum containers, remained fixed at the geometric center of the container (Vatankhah et al, 2015(Vatankhah et al, , 2016.…”
Section: Re Sults and Discussionsupporting
confidence: 57%
“…As reported in the open literature, the position of the slowest cooling zone is usually located at 75 % to 80 % of the container height. However, by increasing the fluid viscosity, the slowest cooling zone tends to be near the geometric center [15,16]. Looking at the literature result and considering the viscosity for the lower shear rate values reported in Fig.…”
Section: Food Products and Containersmentioning
confidence: 75%
“…In addition, Cordioli et al, (2016) raised a very interesting topic on heat transfer by conduction. Their study was used to analyze the effect of gelatinization of modified starch on heat transfer in food systems [73].…”
Section: Cooking and Bakingmentioning
confidence: 99%